2019
DOI: 10.1371/journal.pone.0223209
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarker identification for Friedreich’s ataxia using overlapping gene expression patterns in patient cells and mouse dorsal root ganglion

Abstract: Friedreich’s ataxia (FA) is a neurodegenerative disease with no approved therapy that is the result of frataxin deficiency. The identification of human FA blood biomarkers related to disease severity and neuro-pathomechanism could support clinical trials of drug efficacy. To try to identify human biomarkers of neuro-pathomechanistic relevance, we compared the overlapping gene expression changes of primary blood and skin cells of FA patients with changes in the Dorsal Root Ganglion (DRG) of the KIKO FA mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…DCAKD encodes a protein linked to neurodevelopment ( 57 ) that is expressed widely in the brain ( 58 ), and MCP-GREX of this gene in the caudate basal ganglia was negatively associated with cardiac dysrhythmia ( Table 4 ). Previous studies indicate a relationship between magnetic resonance imaging markers of cerebral small vessel disease and DCAKD ( 59 ) and Friedrich’s ataxia ( 60 ), a disease of progressive neurodegeneration, heart, and spinal problems ( 61 , 62 ). Heart rate variability is thought to represent hyperarousal and has been linked to emotion regulation and chronic pain ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…DCAKD encodes a protein linked to neurodevelopment ( 57 ) that is expressed widely in the brain ( 58 ), and MCP-GREX of this gene in the caudate basal ganglia was negatively associated with cardiac dysrhythmia ( Table 4 ). Previous studies indicate a relationship between magnetic resonance imaging markers of cerebral small vessel disease and DCAKD ( 59 ) and Friedrich’s ataxia ( 60 ), a disease of progressive neurodegeneration, heart, and spinal problems ( 61 , 62 ). Heart rate variability is thought to represent hyperarousal and has been linked to emotion regulation and chronic pain ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, evidence has shown that the ENO2 gene promoter drives high-level transgene expression in differentiated neurons throughout the central nervous system of transgenic zebrafish (Bai et al, 2007). Friedreich's ataxia (FA) is a neurodegenerative disease, and a recent study showed that ENO2 is a marker of mitochondrial function and/or myelination status in FA patients (McMackin et al, 2019). In addition, expression of ENO2 was reportedly linked to prognosis for several cancers, including colorectal cancer (Pan et al, 2020), lung cancer (Liu et al, 2020), and pancreatic cancer (Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies are based on cell types that might be not relevant to analyze neuronal features that are monitored in the clinical scales. In order to bypass this problem, Gino Cortopassi's team have compared the transcriptomic signatures of lymphoblasts and fibroblasts from patients with RNA-seq data from murine frataxin-deficient DRG neurons [209]. This approach allowed the identification in all 3 cell types of common alterations, that might become future biomarkers, in genes involved in mitochondrial stress, apoptosis, oxidative stress, and selenium metabolism.…”
Section: Discussionmentioning
confidence: 99%